تسويق المنتجات الثقافية بالمسارح الجهوية الجزائرية -المسرح الجهوي بالجلفة ''أحمد بن بوزيد'' أنموذجا - عبيدي, فتيحة (جامعة الوادي - University of eloued, 2022)
تسعى المؤسسات الثقافية لإيجاد طرق لتسويق منتجاتها الثقافية، والتي من بينها المسرح الجهوي بالجلفة الذي يعمل على ذلك أيضا، وقد هدفنا من خلال هاته الدراسة إلى اسقاط نموذج COLBERT لتسويق المنتجات الثقافية على المسرح الجهوي بالجلفة، وخلصنا إلى أن المنتج الثقافي بمختلف أنواعه يعاني من مشكلات تسويقية كبيرة، وينعكس ذلك على معظم المؤسسات الثقافية والتي من بينها المسرح الجهوي بالجلفة؛ لذلك تتجه الأنظار حاليًا في ظل الطفرة المعلوماتية، ومع التقدم التكنولوجي الكبير، وزيادة الاعتماد على وسائل التواصل الاجتماعي ومحركات البحث إلى أهمية تفعيل دور التكنولوجيا في المجال الثقافي، وعليه نوصي بأنّ الوسائل التسويقية هي الأمل الكبير الذي تعبُر به الثقافة بالمسرح الجهوي بالجلفة بر الأمان، لتصبح الأكثر تأثيرا في وجدان وعقل المواطن الجلفاوي بصفة خاصة والجزائري بصفة عامة. Cultural institutions are seeking ways to market their cultural products, including the regional theatre of Djelfa. Through this study, we aimed to drop the COLBERT model of marketing cultural products on the regional theater of Djelfa. We have concluded that cultural product of various kinds suffers from significant marketing problems, reflected in most cultural institutions, including the regional theatre of Djelfa. Thus, in the light of the information boom, with the significant technological advances, and increased reliance on social media and search engines, attention is drawn to the importance of activating the role of technology in the cultural field. We, therefore, recommend that marketing means are the great hope for the Regional Theatre of Djelfa to reach safety, becoming the most influential in the conscience and mind of the Djelfa citizen in particular and Algerian in general.
Marketing of cultural products in Algerian regional theatres -The regional theatre of Djelfa “Ahmed Ben Bouzid” as a model
مقال
Keywords: تسويق ; منتج ثقافي ; مسرح ; الجلفة